Molecular Modeling and Prediction of Pharmacokinetics of Some Substituted Benzothiazoles That Block Steroidal Sulphatase Inhibitors for the Treatment of Breast Cancer - Srimathi R (Journal of Global Pharma Technology, 2020)
Objective:Breast cancer is the second leading cause of cancer deaths in women worldwide. Around 60 to 80% of breast cancers are hormone dependent (HDBC). Aromatase and steroidal sulfatase (STS) are targets that increase the concentration of estrogens in circulation, thereby causing breast cancer. At the molecular level, 87% of expression of Steroidal sulfatase is observed and therefore STS is targeted. A series of fifteen substituted 2-phenyl 1,3- benzothiazoles were designed to be an inhibitor of STS, the enzyme responsible for conversion of Estrone sulfate (E1) to Estradiol (E2). Estradiol is the active steroid hormone found in circulation that leads to carcinogensis and results in breast cancer.Materials & Methods:Fifteen substituted 2-phenyl 1,3- benzothiazoles were sketched using Chemsketch (ACD LABS) and 2D structures were saved . The 2D structures were converted to 3D structures with Openbabel and energy minimized using Avogadro. The crystal structure of Human estrone sulfate 1P49 was downloaded from protein data bank (RCSB PDB) and prepared using Protein preparation wizard of Autodock 4.2. The grid box was set at 60*60*60 Å and x=72.242 and y=-1.284, z=28.246 centered on C β atom and docked.Results & Discussion:The docked complex was explored for possible interactions to substituted benzthiazole. Herein, we report the interactions of amino acid residue Arg98, Thr99, His290, Lys368, Thr 91as the best possible interactions that plays a role in inhibiting the binding of Ca2+to the active site. Compound 7C and 8C are reported with better binding affinities.Conclusion:Results obtained from insilico evaluation would provide insights in interaction of benzothiazole with STS explaining its favorable interactions.